Commercial catches and discards composition in the central Tyrrhenian Sea: a multispecies quantitative and qualitative analysis from shallow and deep bottom trawling - TIRALONGO, FRANCESCO; MANCINI, EMANUELE; VENTURA, DANIELE; DE MALERBE, STEPHANIE; PALADINI DE MENDOZA, FRANCESCO; SARDONE, MASSIMILIANO; ARCIPRETE, ROBERTO; MASSI, DANIELA; MARCELLI, MARCO; FIORENTINO, FABIO; MINERVINI, ROBERTO (Mediterranean Marine Science, 2021)
In the Mediterranean Sea, the catch of bottom trawl fisheries is composed of a complex mix of fish and invertebrates with a considerable amount of discards. Seasonal composition of catches and discards of bottom trawls operating at different depths in the central Tyrrhenian Sea were investigated from October 2014 to October 2015. The mean total catch per unit effort (CPUE) ranged between 30.93±8.43 and 27.52±9.88 kg/h in shallow and deep fishing grounds, respectively. The discarded fraction of the catch was 39.9 % in shallow and 43.3% in deep fishing grounds. The mean CPUE of commercial target species were similar in shallow and deep trawling (10.81+5.82 vs 8.92±3.16 kg/h). The commercial bycatch was lower in shallow (6.66±1.25 kg/h) than in deep grounds (8.24±2.91 kg/h), whilst the discards were lower in deep (10.43±5.14 kg/h) than shallow grounds (13.43±5.29 kg/h). Overall, 246 species were caught during fishing operations, out of which 209 were included in discards. The number of species recorded in shallow grounds (199 caught species with 166 discarded) was higher than that recorded in deep grounds (116 caught species with 102 discarded). Fish were the most represented taxa in the shallow discards, followed by echinoderms; crustaceans, and were the main discarded taxa in deep water. Depth was the main factor affecting both commercial catches and discards composition, whereas the season affected the CPUE of main target species only. The results confirmed that discards were higher in shallow than in deep trawling, suggesting that the latter is more efficient than the former in catching fishery resources for human consumption. Understanding the factors that affect discarding is the starting point for adopting management measures to mitigate negative impacts of trawl fisheries on marine resources and benthic communities.